2017
DOI: 10.1111/jcmm.13170
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes derived from miR‐181‐5p‐modified adipose‐derived mesenchymal stem cells prevent liver fibrosis via autophagy activation

Abstract: Proliferating hepatic stellate cells (HSCs) respond to liver damage by secreting collagens that form fibrous scar tissue, which can lead to cirrhosis if in appropriately regulated. Advancement of microRNA (miRNA) hepatic therapies has been hampered by difficulties in delivering miRNA to damaged tissue. However, exosomes secreted by adipose‐derived mesenchymal stem cells (ADSCs) can be exploited to deliver miRNAs to HSCs. ADSCs were engineered to overexpress miRNA‐181‐5p (miR‐181‐5p‐ADSCs) to selectively home e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
273
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 343 publications
(291 citation statements)
references
References 30 publications
8
273
0
Order By: Relevance
“…These results suggest a role for miRNA in the anti‐inflammatory/regenerative function displayed by the CSSC EVs. Such a function is consistent with a number of recent studies that have linked miRNA delivery by EVs to regenerative, antifibrotic, and immune suppressive properties of the vesicles . Some authors have suggested that the small amount of miRNA in EVs makes it more likely that a protein cargo is involved in their biological properties .…”
Section: Discussionsupporting
confidence: 88%
“…These results suggest a role for miRNA in the anti‐inflammatory/regenerative function displayed by the CSSC EVs. Such a function is consistent with a number of recent studies that have linked miRNA delivery by EVs to regenerative, antifibrotic, and immune suppressive properties of the vesicles . Some authors have suggested that the small amount of miRNA in EVs makes it more likely that a protein cargo is involved in their biological properties .…”
Section: Discussionsupporting
confidence: 88%
“…The proteins and/or miRNAs carried by ADSC exosomes may be associated with the promotion of cell protection and angiogenesis. It has been reported that exosomes from ADSCs have therapeutic effects in many diseases, including AMI [22-27]. …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, potential future therapies for DS-AD could be to actively deliver certain miRNAs to the brain, to activate autophagy and remove AD pathology. This approach has been studied for different types of cancer (Qu et al 2017), but has not, to our knowledge, been applied to neurodegenerative conditions and may represent an exciting and novel use for exosomes. Thus, there is a strong connection between autophagy and oxidative stress, which in turn have significant direct and/or indirect effects on exosome cargo and on exosome secretion.…”
Section: Introductionmentioning
confidence: 99%